What One Might Expect: A Scoping Review of the Canadian Policing Research Literature - Huey, Laura (2016)
Using the medium of a scoping review, the author provides an analysis of the Canadian policing research literature published over the past ten years (2006-2015). What this analysis reveals is both expected and unexpected. In line with public views expressed by a number of sources (academics, policy-makers and police), the overall volume of literature produced during this period was low (some 188 (n=188) papers were identified). However, in contrast to the belief expressed by some that the Canadian policing literature is overly theoretical and largely qualitative, the bulk of studies examined (n=123) were quantitative, and eighteen (n=18) were experimental or quasi- experimental in design. Of more critical import, however, is the issue of overall production and lack of coverage of key policing topics. Gaps in topic coverage are explored here, with some key recommendations offered for improving Canadian output